EDUCATIONAL TECHNOLOGY UNDERGRADUATE DEGREE TRACER STUDY TOWARDS SKILLS AND JOBS PERSPECTIVE - Setiawan, Budi -; Fathoni, Toto -; Sukirman, Dadang - (EDUTECH, 2021)
One indicator of a good education system is the existence of a system that is used to measure the output of education itself. Determination of measurements to determine the quality of graduates or alumni include the achievement of graduate competencies, the problems faced can be solved, the career achievements of graduates, as well as things that are either in alignment or not in harmony with the quality of alumni with the quality expected by the university. A good and intact education system has a loop-shaped educational system flow. The education system is the responsibility of universities to students, not ending when students have graduated from college, but also related to the career sustainability of graduates or alumni who are more ready to enter the community. College tracer study is one way to find out the role of alumni in society. Based on the characteristics of alumni or graduates of the Education Technology Study Program, the number of graduate data is 90 people and those who enter fill out questionnaires. Alumni or graduates who filled out the questionnaire were 90 people consisting of (70%) women and (30%) men. Alumni or graduates of the Education Technology Study Program have a study graduation time of 90%, meaning no more than 8 semesters, while 10% do not graduate on time, meaning more than 8 semesters. Alumni or graduates of the Education Technology Study Program overall average GPA of the highest respondents are respondents who have a GPA above 3.5. Alumni or graduates of the Education Technology Study Program show that the highest average employment status is respondents who work. Alumni or graduates of the Education Technology Study Program with the criteria for institutions/institutions/companies that graduates work show the highest average graduates work in private institutions/institutions/companies.